If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2(t + -3) = -8t Reorder the terms: 12 + -2(-3 + t) = -8t 12 + (-3 * -2 + t * -2) = -8t 12 + (6 + -2t) = -8t Combine like terms: 12 + 6 = 18 18 + -2t = -8t Solving 18 + -2t = -8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8t' to each side of the equation. 18 + -2t + 8t = -8t + 8t Combine like terms: -2t + 8t = 6t 18 + 6t = -8t + 8t Combine like terms: -8t + 8t = 0 18 + 6t = 0 Add '-18' to each side of the equation. 18 + -18 + 6t = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 6t = 0 + -18 6t = 0 + -18 Combine like terms: 0 + -18 = -18 6t = -18 Divide each side by '6'. t = -3 Simplifying t = -3
| 5y-12= | | -25y+18=-15y-25 | | x^2+16-28=0 | | 5x-0.8=-0.2+3x | | 4x+4=9x | | (7x+5)(3x-8)= | | x+[x+1]=1.10 | | y=-5+2(-2) | | a^2+10ab+25b^2-49=0 | | (x+49)(x+4)=O | | x^2-5x+6.25-14=6.25 | | 1x-2y=10 | | w+9=-7 | | 5-4x=x-1.5 | | 5x-0.8=0.2+3x | | 6y-1y-12= | | =6z-(3z-6)+(7-8z) | | 15=3x-6x-3 | | 6y^2+8y-9y-12= | | X+x+1+x+2=274 | | -36=p-6 | | 3=18x+6x^2 | | G(x)=8sin(5x^6) | | 6y^2+8y-8y-12= | | k^2+12k=-35 | | 2x^3-2x^2+7x-40=0 | | 9d+d-d+2-3d=0 | | 6y^2+8y-12= | | (49x^2)-(25)=0 | | 3(x+y)-2(2y+x)+y= | | 1+n/3=-6 | | 2x+8+2x=10+2x+12 |